Endovascular salvage of renal and common iliac artery malperfusion following inadvertent hybrid arch dissection stent deployment in the false lumen during repair of type A dissection - Rudra Pandya, BSc; Luc Dubois, MSc; Oonagh Scallan, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
This case report describes the endovascular management of a hybrid arch dissection stent inadvertently deployed in the false lumen during acute type A aortic dissection repair, resulting in renal and lower extremity malperfusion. Prompt identification and intervention are essential to minimize the morbidity and mortality associated with malperfusion. Various endovascular strategies exist to restore perfusion, and this case highlights a unique approach given the obliteration of the true lumen proximally and anatomy of the visceral ostia predominantly originating from the false lumen.